Проблемы методологии в изучении истории - Сарманов, Я.О. (My University, 2016)
Today our society again, appeared before the choice of new trajectories of education, including directions of study of history, development of historical knowledge of students. The analysis of maintenance of state educational standard for histories and correlation of him with the distinguished educational time allows to establish the origin of danger of loss of not only the article of history but also effectiveness of his teaching. The program plugs in itself the methodological and theoretical problems of historical science, classification of historical sources and historiography, description of history of Kazakhstan as parts of world history. It practically impracticable, or superficial illumination of all problems supposes only, that does not answer the requirements of competence education obviously. Therefore to date the actual is remained by the task of fundamental alteration of the folded system of education.
Keywords: trajectory; education; competence